Relation between preoperative autonomic function and blood pressure change after tourniquet deflation during total knee replacement arthroplasty - Huh, In Young; Kim, Dae-Young; Lee, Ji-Hyeon; Shin, Soo Jin; Cho, Young Woo; Park, Soon Eun (Korean journal of anesthesiology, 2012)
Tourniquets are used to provide a bloodless surgical field for extremities. Hypotension due to vasodilation and bleeding after tourniquet deflation is a common event. Hemodynamic stability is modulated by the autonomic nervous system (ANS). Heart rate variability (HRV) is a sensitive method for detecting individuals who may be at risk of hemodynamic instability during general anesthesia. The purpose of this study was to investigate ANS function to predict hypotension after tourniquet deflation. Eighty-six patients who underwent total knee replacement arthroplasty (TKRA) were studied. HRV, systolic blood pressure variability (SBPV) and baroreflex sensitivity (BRS) were analyzed. We assigned two groups depending on the lowest systolic blood pressure (SBP) or mean BP (MBP) after tourniquet release (Group H; SBP < 80 mmHg or MBP < 60 mmHg, Group S; SBP > 80 mmHg and MBP > 60 mmHg). Fifteen patients developed severe hypotension and ten patients were treated with ephedrine. Of the parameters of HRV, SBPV, and BRS, only BRS(SEQ) was significant being low in Group H. BRS and high-frequency SBPV were correlated with the degree of MBP change after tourniquet deflation. Preoperative low BRS is associated with hypotension after tourniquet deflation, suggesting the importance of baroreflex regulation for intraoperative hemodynamic stability.